Effect of subtetanic neuromuscular electrical stimulation on sprint interval exercise - Takeda, Ryosuke; Nojima, Hiroya; Nishikawa, Taichi; Watanabe, Kohei (International Journal of Sports Medicine, 2024)
The study aimed to determine the acute effects of subtetanic neuromuscular electrical stimulation (NMES) combined with active recovery between sprint exercises on blood lactate accumulation, sprint performance, and muscle fatigue. Sixteen healthy young individuals [23(4) years, 10 males] underwent a 1-min rest followed by sprint interval training consisting of four 15-sec maximal sprint exercises with three 5-min active cycling sessions. Participants engaged in voluntary cycling at 40% of peak oxygen consumption, with or without NMES (VOLES or VOL; interventions). Blood lactate concentration ([La]b) was assessed at the end of the rest and each intervention periods. Mean power was assessed during each sprint exercise session. Maximum voluntary contraction (MVC) of the knee extensor was measured before and after sprint interval training to evaluate muscle fatigue. The [La]b was significantly higher in VOLES than in VOL (main effect, P=0.037). Mean power did not differ between conditions (main effect and interaction, P>0.050). MVC after sprint interval exercise was significantly lower in VOLES than in VOL (interaction, P<0.001). Subtetanic NMES combined with voluntary cycling enhanced blood lactate accumulation and induced greater voluntary fatigue but resulted in similar peripheral muscle fatigue and sprint exercise performance compared with voluntary cycling without NMES.
Keywords: subtetanic neuromuscular electrical stimulation; blood lactate accumulation; muscle fatigue; high-intensity exercise